Seedling-growing tray made of rice straw for maize seedling transplantation and its shear mechanics test - Yongcai, Ma; Wei, Zhang; Chun, Wang; Xin, Mao; Bo, Zhang; Haiyang, Wang (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: The plant-made seedling-growing tray cultivation technique is an effective way to improve maize yield and quality in China’s cold northern area. However, the corn seedling nursery carrier and tray cultivation technique has been proved poor in adaptability. After comparing several nursery carriers, a design for a plant-made seedling-growing tray that is suitable for maize transplantation was proposed in which rice straw was used as the primary raw material. The preparation method, processing and structural dimensions of the tray were investigated and designed, five types of plant-made seedling-growing trays with different formulations were proposed. The shear mechanical properties and the shear strength of the plant-made seedling-growing trays were tested to determine the shear force needed for cutting through trays prepared with increasing mass ratios of rice straw and the effect of the shearing rate on the shear strength. The results showed that at a shearing rate of 100 mm/min, the maximum shear force decreased gradually as the mass ratio of straw was increased and that the hardness of the tray decreased as its shear strength decreased. Under three shearing rates (100 mm/min, 200 mm/min and 500 mm/min) and a blade displacement of 10 mm, the shear force was the highest at the point at which the tray was cut through; the required shear force to cut through the tray then gradually decreased. Trays with the same straw composition showed no significant influence of shearing rate on the tray’s shear strength at shearing rates of 100 mm/min, 200 mm/min or 500 mm/min. This study describes a multi-tray, single-strip nursery carrier for use in plant-made seedling-growing tray cultivation and proposes a theoretical basis for the design of a rotary transplanting device, the key part of a maize plant-made seedling-growing tray transplanter. Keywords: maize seedling transplanting, seedling-nursery tray, preparation, shear force, shear strength, rice straw, mixing ratio DOI: 10.3965/j.ijabe.20160906.2222 Citation: Ma Y C, Zhang W, Wang C, Mao X, Zhang B, Wang H Y. Preparation of a seedling-growing tray made of rice straw for maize seedling transplantation and its shear mechanics test. Int J Agric & Biol Eng, 2016; 9(6): 44－55.